Peran TNI Terkait Kejahatan Teroris dalam Upaya Mendukung Kebijakan Pemerintah - Rosmaida, Erviyanti; Triadi, Irwan (Rechtsregel : Jurnal Ilmu Hukum, 2024)
This research aims to clarify the authority of the Indonesian National Army (TNI) in eradicating acts of terrorism and the role of the TNI in supporting government policies in eradicating acts of terrorism in Indonesia. The method used in this research is normative juridical legal research, especially regarding the limitations of the TNI's role in eradicating criminal acts of terrorism. The approach used in this research is a normative juridical approach and a conceptual approach. The research results show that in implementing the TNI's functions and duties in eradicating acts of terrorism, the government must formulate and establish legal standards in detail and not conflict with the provisions of applicable laws and regulations. In the criminal justice system and the TNI must obey the military justice system. Therefore, the Presidential Decree states that the principle of legal certainty must be prioritized in carrying out the TNI's role in eradicating acts of terrorism and especially legal ambiguity which can weaken criminal law and must be prioritized if violations occur. The promulgated Presidential Decree provides clear and detailed indications regarding threats to the state, parameters for escalating the level of terrorist threats, legal regulations regarding the professionalism and criminal responsibility of the TNI for participating in public or political life in the civilian domain of government.